2017
DOI: 10.1016/j.appet.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of overweight and obese Australians' views of food addiction

Abstract: 23The concept of food addiction is increasingly used in the academic literature and 24 popular media to explain some forms of overweight and obesity. However, there is 25 limited evidence on how this term is understood by and impacts overweight and obese 26 individuals. This qualitative study investigated the views of overweight and obese 27 individuals on food addiction, and its likely impact upon stigma, treatment-seeking, and and personal responsibility. Some participants believed "sugar" or "fat" addiction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…Whereas a food addiction explanation for obesity was found to reduce externalized stigma and blame towards a target in one study [45], another study found that labeling an individual as an “obese food addict” created an additive stigma that exceeded the stigma associated with either label on its own [40]. This finding is consistent with a recent qualitative study of individuals with obesity, which noted that some individuals who personally identified with the concept of food addiction felt reluctant to be described as an “addict” because they believed the label would increase self-stigma and stigma from others [43]. Interestingly, the one study identified through our scoping review that examined the association between food addiction and externalized stigma in a clinical sample found that patients with greater severity of food addiction reported greater anti-fat attitudes towards other individuals with excess weight [39].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Whereas a food addiction explanation for obesity was found to reduce externalized stigma and blame towards a target in one study [45], another study found that labeling an individual as an “obese food addict” created an additive stigma that exceeded the stigma associated with either label on its own [40]. This finding is consistent with a recent qualitative study of individuals with obesity, which noted that some individuals who personally identified with the concept of food addiction felt reluctant to be described as an “addict” because they believed the label would increase self-stigma and stigma from others [43]. Interestingly, the one study identified through our scoping review that examined the association between food addiction and externalized stigma in a clinical sample found that patients with greater severity of food addiction reported greater anti-fat attitudes towards other individuals with excess weight [39].…”
Section: Discussionsupporting
confidence: 80%
“…Additional articles supported early intervention efforts through increased regulation of pleasurable foods in children and youth settings such as schools, implementation of programs promoting healthy eating and food choices, and engagement of pediatricians and family physicians [65,66]. In contrast, a recent qualitative study with 23 individuals with obesity showed that individuals were skeptical about the effectiveness of restrictions on highly pleasurable foods, although they supported addictive food restrictions for children [43]. Nonetheless, reviews generally supported external control of addictive foods based on examples where cigarette smokers perceived external control as being influential or effective compared to individual motivating factors (e.g., willpower, personal choice) [67,68].…”
Section: Resultsmentioning
confidence: 99%
“…These include: (1) eating disorders such as bulimia nervosa (BN) and binge eating disorder (BED); (2) obesity; and (3) food addiction (FA), which have very different diagnostic considerations (Table 1). However, is it important to acknowledge that the validity of FA is a highly debated and controversial concept within the scientific community (Ziauddeen and Fletcher, 2013; Hebebrand et al, 2014; Cullen et al, 2017). In this review article, we examine the cognitive underpinnings of this transdiagnostic compulsive eating phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Research has documented a wide range of contemporary perspectives connected to obesity (Curtis & Davis, 2014;Duarte, Pinto-Gouveia, & Ferreira, 2014;Hernandez-Hons & Woolley, 2012 a diagnostic approach using defining terms such as "binge eating" or "food addiction" (Curtis & Davis, 2014;Duarte et al, 2014). The concept of "food addiction" is increasingly employed in the academic literature, (Cullen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%